The Significance of Subtlety: Contrasting Lithic Raw Materials Procurement and Use Patterns at the Oldowan Sites of Barranco León and Fuente Nueva 3 (Orce, Andalusia, Spain) - Barsky, Deborah; Titton, Stefania; Sala-Ramos, Robert; Bargalló, Amèlia; Grégoire, Sophie; Saos, Thibaud; Serrano-Ramos, Alexia; Oms, Oriol; Solano García, Jose-Antonio; Toro-Moyano, Isidro; Jiménez-Arenas, Juan Manuel (Frontiers in Earth Science, 2022)
Situated in southern Spain's Guadix-Baza basin, Barranco León and Fuente Nueva 3 (Orce, Andalusia, Spain) are two of the most important western European Oldowan archeological sites. After 30 years of quasi-uninterrupted excavations, these two occurrences have yielded exceptional lithic and faunal records in precisely dated stratigraphic situations, providing a wealth of information about the oldest presence of hominins outside of Africa (1.4 and 1.3 Ma, respectively). Recently, excavations and multidisciplinary research have allowed to discern new patterns of lithic raw material procurement and use patterns practiced by the Orce hominins that enable us to clearly distinguish different behavioral patterns between these two sites; in spite of their spatial proximity. This paper explores new data from the lithic collections in relation to hominin technical and economic behavior, highlighting subtle but significant differences in their exploitation of local limestone and flint clasts more than a million years ago. During this period of the late Early Pleistocene, these sites were situated on the shores of an ancient saline lake surrounded by thermal fresh water sources. This favorable environmental situation, while attractive to the hominins, also supported life for an abundance of large mammals, including competitive large carnivores, underlining questions of expedience as an influence on techno-morphology in these early stone toolkits. This paper analyzes these themes, highlighting updated information from these and other key European late Early Pleistocene sites.